The improvement on enzymatic hydrolysis of oil palm (Elaeis guineensis) empty fruit bunch lignocellulose - Nurul Adela, B.; Loh, S.K.; Nasrin, A.B. (Penerbit Universiti Kebangsaan Malaysia, 2015)
The lignocellulose constituents of oil palm biomass have potential as substrates for sugar and bioethanol production. Research focusing on this indicated that high enzyme loading may hinder large-scale utilisation. Thus, attempts improving the enzymatic saccharification of the acid-pretreated empty fruit bunches (EFB) were made by investigating enzyme (cellulase) concentrations and combinations, and co-existence of enzyme with catalysing agents e.g. metal ions and surfactants. The study revealed that a combined Celluclast 1.5 L: Cellic CTec of 30 FPU/g: 1% (v/v) gave the optimum glucose yield of 307.3 ± 3.5 mg/g. The presence of 10 mM cobalt ion and 0.5% (v/v) Triton X-100 enhanced cellulose conversion by 16.2% and 38.4%, respectively. Overall, an addition of non-ionic surfactants gave the most satisfied cellulose conversion (83.8%) corresponding to 567.2 ± 28.4 mg/g of glucose yield from the pretreated EFB. This improved enzymatic saccharification can be utilised to enhance the production of second generation bioethanol, particularly from oil palm biomass.